2020
DOI: 10.1108/oir-08-2020-0331
|View full text |Cite
|
Sign up to set email alerts
|

Research information encountering and keeping behaviour of post-graduate students of social sciences in an online environment

Abstract: PurposeLiterature divides information behaviours into two forms: first, interacting information with a purpose in mind and second, encountering accidently in three environments including person to person, analogue and online environment. However, the unique information encountering and encountered information keeping behaviour of social sciences research students of Asian culture in an online environment remained unexplored. Therefore, the present study is designed to investigate the research information encou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Literature reveals that many scholars applied purposive sampling in their quantitative studies (Awan et al. , 2021; Naicker, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature reveals that many scholars applied purposive sampling in their quantitative studies (Awan et al. , 2021; Naicker, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Third, no study examined the mediating role of employee creativity in the relationship between employees' intrinsic motivation and job performance in the Indian retail industry. Literature reveals that many scholars applied purposive sampling in their quantitative studies (Awan et al, 2021;Naicker, 2018). According to Crossman (2017), "the purposive sampling technique is commonly used to generate reviews of events or experiences, which is to say, it is common to studies of particular groups within larger populations."…”
Section: Research Methods and Data Collectionmentioning
confidence: 99%
“…These Findings are matched with the findings of previous research. Researchers investigated information keeping behavior of encountered information and concluded less use of digital notebook app among Pakistani research students (Awan et al, 2020). Ullah et al (2016) have different point of view, as they concluded that majority of Pakistani students were satisfied with PIM app namely “StudentPIM” and they also supported the “simplicity and usability” of this app.…”
Section: Discussionmentioning
confidence: 99%
“…However, those who use the internet for general browsing encounter more than those who purposively. Thus, the IE model is also equally applicable to researchers who generally browse other than purposively looking for information (Awan et al, 2020). A study by Lueg and Twidale (2018) put stress on the designing and developing interfaces that are effective at supporting specific needs of humans, but there are many complications in developing interfaces that reflect key human characteristics and strengths.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Their study defines the purposive information behavior exists in two forms: first when information is looked for with a clear purpose and second when information is accidentally or serendipitously encountered (Awan et al, 2020).…”
Section: Serendipity and Information Encountering In Researchmentioning
confidence: 99%